"A Multi‐center, randomized, double blinded, comparative study of two hyaluronic acid fillers for temporary restoration of mid‐face volume in Asians". (26th November 2019) - Jung, Joon Min; Lee, Woo Shun; Kim, Hak Tae; Moon, Young Seon; Paik, Seung Hwan; Lee, Woo Jin; Chang, Sung Eun; Lee, Mi Woo; Won, Chong Hyun; Kim, Beom Joon
Abstract: Background: There have been few studies using hyaluronic acid fillers to restore mid‐face volume deficit especially in Asians. Aims: This study compared the efficacy and safety of two highly cohesive hyaluronic acid fillers, Neuramis® Volume Lidocaine and Juvederm® Voluma® with Lidocaine (VYC‐20L), for temporary restoration of mid‐face volume in Asians. Patients/Methods: A total of 88 subjects with moderate to severe age‐related mid‐face volume deficit on the Mid‐Face Volume Deficit Scale (MFVDS) received Neuramis® Volume Lidocaine on one side and VYC‐20L on the other side of the face. Response was defined as a ≥1 point reduction in MFVDS at 24 weeks after the injection by photographic assessment. Secondary end points included photographic and live assessments of MFVDS and its changes at week 4, 12, and 24; global aesthetic improvements, as assessed by the investigators and the subjects at each visit; and the proportion of subjects who received touch‐up treatment. Results: The response rates of the sides treated with Neuramis® Volume Lidocaine and VYC‐20L were identical (96.39%) at week 24, demonstrating that Neuramis® Volume Lidocaine was noninferior to VYC‐20L. Photographic and live assessments of MFVDS and its changes, global aesthetic improvement, and the proportion of subjects who received touch‐up treatment did not differ significantly during follow‐up. Conclusions: Neuramis® Volume Lidocaine was not inferior to VYC‐20L in temporarily restoring mid‐face volume at 24 weeks after treatment. Both of these highly cohesive hyaluronic acid fillers can be used effectively and safely for the correction of mid‐face volume loss in Asians.